People living with moderate-to-severe COPD prefer improvement of daily symptoms over the improvement of exacerbations: a multicountry patient preference study. Issue 2 (13th June 2022) - Cook, Nigel S.; Criner, Gerard J.; Burgel, Pierre-Régis; Mycock, Katie; Gardner, Tom; Mellor, Phil; Hallworth, Pam; Sully, Kate; Tatlock, Sophi; Klein, Beyza; Jones, Byron; Le Rouzic, Olivier; et al.
Introduction: This patient preference study sought to quantify the preferences of people living with COPD regarding symptom improvement in the UK, USA, France, Australia and Japan. Methods: The inclusion criteria were people living with COPD aged 40 years or older who experienced ≥1 exacerbation in the previous year with daily symptoms of cough and excess mucus production. The study design included: 1) development of an attributes and levels grid through qualitative patient interviews; and 2) implementation of the main online quantitative survey, which included a discrete choice experiment (DCE) to allow assessment of attributes and levels using hypothetical health state profiles. Preference weights (utilities) were derived from the DCE using hierarchical Bayesian analysis. A preference simulator was developed that enabled different health state scenarios to be evaluated based on the predicted patient preferences. Results: 1050 people living with moderate-to-severe COPD completed the survey. All attributes were considered important when patients determined their preferences in the DCE. In a health state preference simulation, two hypothetical health states (comprising attribute levels) with qualitatively equivalent improvements in A) cough and mucus and B) shortness of breath (SOB) resulted in a clear preference for cough and mucus improved profile. When comparing two profiles with C) daily symptoms improved and D) exacerbations improved, there was a clear preference for the daily symptoms improved profile. Conclusions: People living with moderate-to-severe COPD prefer to reduce cough and mucus production together over improvement of SOB and would prefer to reduce combined daily symptoms over an improvement in exacerbations. There is a need for symptom-focused therapies to deliver meaningful outcomes for people living with COPD https://bit.ly/3KqcSur